High content of constitutive heterochromatin in two species of Pseudonannolene (Diplopoda) - Da Silva Souza, Tatiana [UNESP]; Prado, Rogilene Aparecida [UNESP]; Fontanetti, Carmem S. [UNESP] (Firenze University Press, 2004)
Due to the fact that a considerable amount of constitutive heterochromatin has been commonly found in millipedes, this paper presents the characterization of the chromosomal complement, through C-banding technique, of two species of millipedes belonging to the genus Pseudonannolene. The species Pseudonannolene tocaiensis shows 2n=20, with five chromosomal pairs almost completely heterochromatic and the remaining pairs with pericentromeric C+ blocks. P. silvestris shows 2n=16, with a large heterochromatic portion in the first two pairs of autosomes, which presented the long arms totally C+.
Keywords: Constitutive heterochromatin; Cytogenetics; Diplopoda; Pseudonannolene